CRIMINATION OF CRIMINAL ACTS OF KHAMAR AND DRUGS IN ISLAMIC CRIMINAL LAW COMPARED TO INDONESIAN POSITIVE CRIMINAL LAW - Hulaimi Hulaimi; Lewiaro Laia; Khairul Azwar Anas (PENA LAW: International Journal of Law, 2022)
Narcotics and dangerous drugs may be as old as humans. Increasingly, drug users are increasingly widespread in various parts of the world, including Indonesia. The types of drugs are getting more and more sophisticated. In this latest century, it seems that no country is free from the problem of drugs. The term drugs in the context of Islamic law, is not mentioned directly in the Qur'an or in the Sunnah. In the Koran only mentions the term khamr. The purpose of this study is to analyze the comparison of punishment for perpetrators of the crime of alcohol and drugs in Islamic criminal law compared to positive Indonesian criminal law with normative legal research methods. The criminal difference for the perpetrators of the crime of khamr in Islamic criminal law compared to positive Indonesian criminal law is that in Islamic law, the punishment imposed is only in the form of caning, while in positive Indonesian criminal law, the sentence imposed can be in the form of imprisonment or a related fine. with liquor which is classified as a "crime" and imprisonment or a fine related to liquor which is classified as an "offence". Sanctions for perpetrators of drug abuse in the perspective of Islamic criminal law, have similarities with the legal sanctions for criminal acts of drug abuse in the perspective of the criminal law of the Republic of Indonesia, namely both are the authority of the government/judges to determine the punishment.